2018
DOI: 10.1159/000489766
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-33 Predicts Poor Prognosis and Promotes Renal Cell Carcinoma Cell Growth Through its Receptor ST2 and the JNK Signaling Pathway

Abstract: Background/Aims: Renal cell carcinoma (RCC) is currently the ninth most common cancer in men. Interleukin (IL)-33 expression has previously been associated with a number of cancers; however, its biological role in RCC is poorly understood. In this study, we sought to elucidate the role of IL-33 in RCC. Methods: Serum IL-33 levels were measured by ELISA. IL-33 expression in clinical RCC samples was examined by immunocytochemistry. The proliferation and apoptosis rate of RCC were determined by CCK8 and flow cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…The latter is a highly conserved signal transduction in eukaryotic cells and one of the best-characterized signaling cascades to regulate cell proliferation (Achkar et al, 2018;Liu et al, 2018;Liang and Yang, 2019). A number of studies have demonstrated a role for the increased activity of MAPK signaling cascades in RCC cells and activation of the MAPK pathway was generally recognized for RCC growth (Wu et al, 2018;Zhao et al, 2018). Our current data further support this notion.…”
Section: Discussionsupporting
confidence: 81%
“…The latter is a highly conserved signal transduction in eukaryotic cells and one of the best-characterized signaling cascades to regulate cell proliferation (Achkar et al, 2018;Liu et al, 2018;Liang and Yang, 2019). A number of studies have demonstrated a role for the increased activity of MAPK signaling cascades in RCC cells and activation of the MAPK pathway was generally recognized for RCC growth (Wu et al, 2018;Zhao et al, 2018). Our current data further support this notion.…”
Section: Discussionsupporting
confidence: 81%
“…In colon, IBD is a major risk factor of colorectal cancer with 23-fold increased risk among patients with pancolitis (17). In addition, IL-33 up-regulation has been detected in established invasive cancers, which may suggest a role for IL-33/Treg axis in tumor progression in response to damaged tissue homeostasis (9,(18)(19)(20). These observations suggest IL-33 blocking antibodies developed for atopic disorders may show efficacy in cancer treatment.…”
Section: Il-33 and Tregs Are Increased In Cancer-prone Chronic Inflammentioning
confidence: 99%
“…Such over-expression was associated with advanced tumor-lymph node-metastasis (TNM) stage, resulting in reduced survival and increased risk of recurrence in patients. Mechanistically, it has been shown that IL-33 enhances RCC cell growth in vivo and prevents chemotherapy-induced tumor apoptosis in vitr o via JNK signaling activation in tumor cells ( 149 ). Similarly, both IL-33 and ST2 were up-regulated in ovarian tumors compared to normal ovary and ovarian benign tumors, and the expression levels were further increased in tumor tissues at the metastatic site ( 150 ).…”
Section: Il-33/st2 As a Biomarker Predictive Of Cancer Progression Anmentioning
confidence: 99%